REALISASI JANJI KAMPANYE PROGRAM KESEHATAN BUPATI SEMARANG PERIODE 2010-2015 - Fatmawati, Agustin Maharani; ., Turtiantoro; Harsato, Priyatno (Journal of Politic and Government Studies, 2014)
ABSTRACTIONHealth program is the flagship program of the couple Mundjirin and Warnadi. Health programs are favored free treatment at health centers and classrooms III general hospitals. This study uses qualitative methods research that produces descriptive data described with words written and spoken by the people as well as observations of behavior to determine how the realization of campaign promises the couples Mundijirin and Warnadi in elections of regional heads Semarang district 2010. The results showed that the campaign promises of health programs in the form of Semarang regency regent free health programs truly realized.Keywords : Campaign Promises, Health Programs, The Realization